A Clinical Guide to the Treatment of the Human Stress Response - Everly, George S.; Lating, Jeffrey M. (Springer, 2013)
The idea for our original volume fi rst arose in 1979. At that time, the study of human stress was by no means new. More than four decades earlier, the brilliant endocrinologist Hans Selye had coined the term “stress” and along with Harvard’s Walter Cannon had pioneered the study of its then perplexing physiology. John Mason, at Yale, had not only expanded the work of Selye and Cannon but also offered a heuristic formulation that made the physiology, especially the endocrinology, of stress accessible to even the non-physiologist. In 1939, the Journal of Psychosomatic Medicine was fi rst published and offered explorations of the interrelationships between psychological and physiological processes, with the subsequent goal to integrate somatic and psychologically anchored therapies. Thus the basis for the science and practice of what some would later call “psychosomatic medicine” and later “stress medicine” was established. The late 1960s and early 1970s saw a virtual “epidemic” of stress-related physical and psychiatric disorders. Whether it was truly an increase in the incidence of such disorders or simply an increased acuity in the recognition of such disorders is unclear. Nevertheless, psychiatrists, psychologists, and non-psychiatric physicians were being challenged with patients who clearly presented with disorders of over arousal and disturbances in mind-body relationships. Traditional patterns of medical practice for stressrelated illnesses typically focused upon treatment of the end-organ. While this is often useful and necessary, something seemed to be missing in the treatment mosaic. One of the fi rst groups to recognize this omission was the interdisciplinary group at Harvard Medical School headed by Herbert Benson. Benson, Joan Borysenko, David Eisenberg, and others who were predecessors or contemporaries of that group including Paul Rosch, Ernst Gellhorn, Gary Schwartz, and Edmund Jacobson, believed that in many instances the most effective treatment for stress-related disorders would be those interventions that served to mitigate pathogenic arousal, not just to mitigate the target organ disease or dysfunction. Sadly, there were no textbooks that attempted to edify and instruct the clinician in the mosaic or continuum of treatments of the human stress response itself, rather than just its somatic and psychological manifestations. The fi rst addition of this book and its predecessor, a volume entitled The Nature and Treatment of the Stress Response , were clinical guides that endeavored to focus on the management and treatment of pathogenic arousal. As a result of its unique focus, earlier versions of this book found a receptive audience. Thus 33 years later, this volume has once again been updated. Its purpose remains the same, that is, to serve as a useful introduction to the psychophysiologic nature of the human stress response, as well as a practical clinical resource for anyone interested in managing or treating excessive stress. This book is designed for students and practitioners in the fi elds of psychology, psychiatry, social work, education, and public health, as well as anyone else seeking a better understanding of the complexities of mind-body relationships and further seeking practical guidelines for intervention. There seems little doubt that such a volume is still needed. The fi eld of disaster mental health continues to grow, terrorism remains a constant concern internationally, volatile economic conditions as well as political unrest have set the foundation for a most anxiogenic world. While the need for a volume such as this seemed great 30 years ago, it seems even greater now as we realize we cannot just continue to solely treat the manifestation of excessive stress, we must treat the pathogenic processes, as well. This is especially true in an environment of rising healthcare costs. Lastly, given the previous discussion, we must look to the final frontier…human resilience. In this volume we examine the notions of psychological immunity and human resilience as we attempt to complete the continuum of care in “stress medicine.”
Keywords: Human stress